In vitro effects of Phaleria macrocarpa (Boerl.) Mahkota Dewa fruit aqueous and methanol-chloroform extracts on glucose uptake and metabolism - Abdullah, Nurul Akmaryanti (2014)
Diabetes mellitus is the most common metabolic disease worldwide. One of the main pathophysiological defects of diabetes is insulin resistance due to impairment in the insulin-signaling pathway leading to a failure of the insulin stimulated glucose uptake in the target cells. Traditionally, plants such as Phaleria macrocarpa have been used to treat diabetes. The mechanism of how this Phaleria macrocarpa exert an anti-diabetic effect still obscure and thus a research consisted of five studies was conducted in vitro with the objectives to evaluate the anti-diabetic properties of Phaleria macrocarpa aqueous and methanol-chloroform fruit extracts using hepatocytes (HepG2 cells) as a model. In these studies, HepG2 cells were cultured in RPMI media in the presence of Phaleria macrocarpa fruit extracts (0, 0.01, 0.1 and 1 mg/mL) or metformin (1 mg/mL) or insulin (100 nM). Metformin and insulin were used as positive control. There are five studies including glucose uptake assay, inhibitor studies using wortmannin (PI3-kinase inhibitor) and genistein (protein tyrosine kinase inhibitor), glycogen synthesis assay and glycogen synthase activity assay. The present studies showed that both Phaleria macrocarpa extracts (aqueous and methanol-chloroform) had demonstrated the ability to enhance glucose uptake activity by up to 5-folds (p<0.05). That is similarly to the metformin when compared to the control. However, insulin showed the highest in glucose uptake activity (7-folds). The efficacy of aqueous extract was found to be slightly better than the commercial drug, metformin. In inhibitors study, the glucose uptake activity in cell cultures pre-treated with wortmannin or genistein and later with Phaleria macrocarpa extracts were significantly reduced (p<0.05) suggesting a possible involvement of PI3-kinase pathway and protein tyrosine kinase pathway in Phaleria macrocarpa-induced glucose uptake activity. The percentages of inhibition at all doses of Phaleria macrocarpa extracts were comparable with the percentage of inhibition on insulin action. These indicated that the Phaleria macrocarpa action was mimicking the action of insulin. Glycogen synthesis was stimulated in HepG2 cells by more than 1-fold after treatment with Phaleria macrocarpa extracts. Metformin showed no effect on glycogen synthesis whereas insulin caused a maximum increased in glycogen synthesis activity in two hours. Both aqueous and methanol-chloroform of Phaleria macrocarpa fruit extracts significantly increased (p<0.05) glycogen synthase activity. The significant changes in enzyme activities were observed at as low as 0.01 mg/mL of Phaleria macrocarpa extracts while the maximum effects was observed at 1.0 mg/mL aqueous extract. This was similar to insulin effect and thus Phaleria macrocarpa was able to increase glycogen synthase activity at the same rate as insulin. Moreover, metformin also demonstrated significant increase in glycogen synthase activity (p<0.05) when compare to control, however its activity was lower than insulin. These studies concluded that Phaleria macrocarpa extracts have the ability to increase glucose uptake, glycogen synthesis and glycogen synthase activity similar to insulin action. Thus, Phaleria macrocarpa fruit extracts have insulin mimic activity. Therefore, with further investigation including clinical trial, Phaleria macrocarpa has a therapeutic potential as an anti-diabetic agents.